Numerical investigation of welding deformation diminution for double shell structure using the layered inherent strain - Cheng Li; Hua Zhai; Lianwei Zhu; Zhihong Liu; Jianguo Ma; Xiaofeng Zhu; Qiong Liu (Nuclear Engineering and Technology)
Cyclotron is a key scientific tool and indispensable research platform for conducting cutting-edge research in nuclear equipment development as well as innovative applications of nuclear technology. The shell component has a double-layer thick-walled structure with intricate ribs and high-density, full-penetration welded joints. The mitigation of welding deformation is of profound significance to the performance of the cyclotron. The thick plate joint has many welding layers which will be divided into several steps to complete the backing, filler, and cap welding. The equivalent transverse and longitudinal plastic strains of different layers were extracted by the thermo-elastic-plastic method. The welding deformation generated by each layer of weld can be predicted by using the equivalent plastic strain, and the total distortion can be accumulated layer by layer. Numerical simulation and experimental studies were conducted on the welding deformation of the double shell specimen, and the welding sequence and design of the welding fixture were discussed in detail. The digital photogrammetry system was used to monitor the deformation state of the welded parts in real-time. The measured deformation was compared with the simulation results. Ultimately, the deformation of the specimen is controlled at 2.64 mm. The proposed method can flexibly evaluate the impact of each welding layer on welding deformation for multiple welds, which can provide technical guidance for cyclotron engineering manufacturing.